Knockout of OsNramp5 using the CRISPR/Cas9 system produces low Cd-accumulating indica rice without compromising yield. Issue 1 (December 2017) - Tang, Li; Mao, Bigang; Li, Yaokui; Lv, Qiming; Zhang, LiPing; Chen, Caiyan; He, Hanjie; Wang, Weiping; Zeng, Xiongfeng; Shao, Ye; Pan, Yinlin; Hu, Yuanyi; et al.
Abstract Rice grain with excessive cadmium (Cd) is a major source of dietary Cd intake and a serious threat to health for people who consume rice as a staple food. The development of elite rice cultivars with consistently low Cd content is challenging for conventional breeding approaches, and new strategies urgently need to be developed. Here, we report the development of newindica rice lines with low Cd accumulation and no transgenes by knocking out the metal transporter geneOsNramp5 using CRISPR/Cas9 system. Hydroponic culture showed that Cd concentrations in shoots and roots ofosnramp5 mutants were dramatically decreased, resulting in rescue of impaired growth in high Cd condition. Cd-contaminated paddy field trials demonstrated that Cd concentration inosnramp5 grains was consistently less than 0.05 mg/kg, in contrast to high Cd concentrations from 0.33 mg/kg to 2.90 mg/kg in grains of Huazhan (the wild-typeindica rice). In particular, the plant yield was not significantly affected inosnramp5 mutants. Furthermore, we developed promising hybrid rice lines with extremely low Cd content in grains. Our work supplies a practical approach to developing Cd pollution-safeindica rice cultivars that minimizes Cd contamination risk in grains.